HYDROPONICS TECHNOLOGY TO GROW PLANTS WITHOUT SOIL - P. V. Shishkin; O. V. Antipova (Овощи России, 2017)
The method of hydroponics for growing plants without soil has been developed, where the many advantages are: the high technological performance; reduce of expenses; economy in watering and fertilizers due to lack of drainage system and extra engineering needed for solution circulation; reduce of exploitations expenses due to lack of soil tilling. There is also no problem concerning the root rots that are typical for all methods of growing plants without soil. This allows growing the plants with large root volume and prolonged period of vegetation. Efficiency of this system  has been proven by multi-year experiments. It was shown  that  vegetable crop  such as cucumber,  the root system of which is very sensible to oxygen deficiency, well grew, developed and gave fruits on the vegetation tray.